Treatment of a Symptomatic Forearm Muscle Herniation with a Wrap-Around Fascia Lata Graft - Khalid, Kamarul Ariffin; Mah, Edward T (Springer, 2009)
Muscle herniation in the extremity is a well recognized cause of symptomatic pain on exertion. Only 17 cases involving the upper limb has been previously described, 11 of them involving the anterior compartment of the forearm and only 2 were caused by strenuous exertion. Treatment for this condition ranged from nonsurgical, primary closure with palmaris longus interweave, formal fasciotomy, to closure with a tensor fascia lata graft. This is a study of a 28-year-old man who had a symptomatic swelling on the volar aspect of his left forearm while working on a car-door assembly line that resulted in a significant decreased of his grip strength, work capacity and median nerve symptoms. It did not improve after 6 months of conservative management including hand therapy and splintage. The patient subsequently underwent a tensor fascia lata graft wrap-around. Postoperatively his symptoms resolved with improvement in his grip strength and hand function. The rationale for the treatment option chosen is discussed.